Fatty Acids Composition of Red and Purple Pomegranate (Punica granatum L) Seed Oil - Soetjipto, Hartati; Pradipta, Murda; Timotius, KH (Indonesian Journal of Cancer Chemoprevention, 2010)
The aim of this investigation was to determine the content and composition ofÃÂ  fatty acid in seed oil of red and purple pomegranate (ÃÂ  Punica granatum L). The extraction process was performed by Soxhlet extractor with petroleum ether as solvent. The separation and identification of pomegranate seed oil was done by using GCMS. The total oil content of red and purpleÃÂ  pomegranateÃÂ  were 128 g/kg d.wÃÂ  and 103 g/kg d.w respectively. Both showed the same major fatty acidsÃÂ  as palmitic, stearic, oleic, linoleic andÃÂ  punisic acid. Oleic acid ( 19-21% ) and linoleic acid ( 20-21% ) were found as the mostÃÂ  dominant fatty acids in red pomegranate, whereas purple pomegranate seed oil was dominated by oleic acid ( 41-43% ) and punicic acidÃÂ  ( 0-25% ). Neutral lipidÃÂ  fraction ofÃÂ  red and purple pomegranate seed oils was more dominantthan glycolipid and phospholipid. NeutralÃÂ  lipid fractionÃÂ  of red and purple pomegranate seed oil wereÃÂ  89 % and 91% respectively.ÃÂ  Glycolipid fractionÃÂ  of red and purple pomegranate seed oil were 8 % and 5 % , whereas phosholipid fraction of red and purple pomegranate seed oil were 3 % and 4 %. The punicic acid content ofÃÂ  total lipid ofÃÂ  purple pomegranate seed oil ( PPSO ) (0-25% ) was higher than red pomegranate ( RPSO ) ( 9-16% ). On the contrary neutral lipid of red pomegranate showed higher punicic acid content (54-75%) than the purple pomegranate (14-55% ). Glycolipid of red pomegranate containedÃÂ  punicic acidÃÂ  ( 0-42%). The punicic acidcontentÃÂ  of the phospholipid fraction ofÃÂ  red pomegranate was higher ( 0-22 % ) than the one ofÃÂ  purple pomegranate (0-2% ).